O papel da mídia sergipana nas estratégias de agendamento na mobilização da dialética global-local a partir de uma situação concreta: as Olimpíadas/2012 - Mezzaroba, Cristiano (2015)
With all the mega sporting events that are happening in Brazil (The 2007 Pan-American Games, The 2013 Confederations Cup, The 2014 World Cup and the 2016 Olympic/ Paralympic Games) it is possible to visualize a profitable and instigator moment for researches around this topic, concentrating our attention at the 2012 London Olympic Games. The exaltation of the sport phenomenon brought, in this research, the multiple sides through which the media can present itself and join itself with (regarding economy, culture, politics, education etc.). Our objective was to analyze how the media in the state of Sergipe anticipated and gave visibility to the 2012 Olympic Games, building a “sports-media scheduling” strategy, from the mobilization of the global-local dialectic. Characterized as a qualitative study, which has a descriptive-exploratory approach, this research was developed in three areas: print media, digital media and broadcast media – which have highlighted the low effectiveness of the scheduling strategy and the global-local dialectic strategy, whether because of amateurism in journalistic entities, or because of lack of interest, since there were no athletes from Sergipe in the competition.________________________________________________________________________________________________________________________________